PENGARUH LAYANAN PENGUASAAN KONTEN UNTUK MENINGKATKAN PEMAHAMAN DIRI TENTANG KETERAMPILAN BELAJAR PADA SISWA KELAS XI IPA SMA NEGERI 8 BENGKULU UTARA: PENGARUH LAYANAN PENGUASAAN KONTEN UNTUK MENINGKATKAN PEMAHAMAN DIRI TENTANG KETERAMPILAN BELAJAR PADA SISWA KELAS XI IPA SMA NEGERI 8 BENGKULU UTARA - Syahriman; Rita Sinthia; Faza Istiana (UNIVERSITAS BENGKULU, 2024)
This study aims to describe the effect of content mastery services to improve the learning skills of grade XI IPA students of SMA Negeri 8 North Bengkulu. This research method uses a one-group pre-test post-test design experiment. The population of this study was the entire class XI of science. The sampling technique used is random intact group sampling. The instrument used in this study was a questionnaire of student learning skills. The data analysis technique in this study uses a Test-test (Paired Sample Test). The results obtained in this study show the influence of content mastery services on students' learning skills. This means that students' learning skills before being given content mastery services are low. Then students' learning skills after being given content mastery services become high. And there is an influence of content mastery services on improving the learning skills of class XI IPA students of State High School. Keywords: content mastery services, self-understanding, students